PENGEMBANGAN SASARAN, VISI DAN MISI HUBUNGAN MASYARAKAT DI LEMBAGA PENDIDIKAN BERBASIS KEPUASAN PELANGGAN - Sutrimo Purnomo (Jurnal Kependidikan, 2017)
An educational institution should try to create an positive image in the heart of the people, so that people are able to make the decision to enroll their children and participate actively in the institution development. Positive image can be realized by developing quality and organizing some productive activities that have public relation with clear vision and mision. This paper offers an alternative for implementation and development of the vision and mision of public relation based on customer satisfaction in order to realize institution positive image. Customer satisfaction can be realized by the commitment in understanding the customer expectation, so education institution need to identify â€œthe needs and pretentionsâ€ of customer expectations. Some things need to be done in improving customer satisfaction related to the development of the vision and mission of public relations, namely: Compiling identification program of costumer expectation, measuring customer satisfaction consistently, designing services based on costumer expectations, communicating effectively, building proactive, friendly, anthusiastic and trust of personal profile, building anorganizational structure that accommodates customer service, and developing participative management.